Reluctant educators and self‐advocates: Older trans adults' experiences of health‐care services and practitioners in seeking gender‐affirming services. (16th July 2020) - Willis, Paul; Dobbs, Christine; Evans, Elizabeth; Raithby, Michele; Bishop, Jenny‐Anne
Abstract: Background: Trans‐identifying individuals experience unique barriers and challenges in negotiating health‐care systems due to the cisnormative attitudes and practices which obstruct the receipt of trans‐inclusive care. To date, there has been little exploration of older trans consumers' experiences of contemporary health‐care services when seeking to transition medically in later life. Objectives: Qualitative findings are presented from a study of trans ageing and trans‐related health and social care needs in Wales, UK (2016‐18). The objectives are to (1) examine supportive and obstructive points of interaction with health‐care professionals, and (2) identify key learning messages for improving trans‐related health care from the perspectives of trans‐identifying adults in later life. Design: Trans‐identifying participants self‐selected to take part in two interviews—a life‐history interview and a semi‐structured interview. Interview data were analysed thematically using the framework method approach. Setting and participants: This paper focuses on the accounts of 19 participants (50‐74 years of age) who identified as trans and were seeking to transition medically in mid‐ to later life. Results: Findings indicate how older trans patients are positioned as reluctant educators for GPs in primary care settings and illustrate the transphobic practices and cisnormative assumptions encountered across health‐care interactions and systems that impede their journey of transitioning in later life. Discussion and conclusions: Messages from this study speak to the importance of improving professionals' knowledge of gender identity diversity across the life course and making changes at a systemic level in redressing cisnormative assumptions and systems that reinforce inequities on the basis of gender identity.